"Vérification des performances de la colonne de débutaniseur au niveau de la section GPL Rhourde- Nouss" - دبيلي, علاء الدين (University of El-Oued, 2021)
"Abstract: The LPG plant facilities are designed to recover LPG and condensate remaining in the gas from phase A (gas treatment and condensate recovery). The exploitation of the RHOURDE NOUSS field (gas and condensate) over time has led to a decrease in the richness of heavy product. This decrease in richness influenced the operating parameters of the unit. Our work consists in making a verification calculation by approximate sizing method on the debutaniser column (T-02) and comparing the results obtained with the design one, to ensure the correct functioning of the column. Keywords: LPG, Condensate, Debutanizer column (T-02), Approximate sizing method." "ملخص : تم تصميم مرافق مصنع غاز البترول المسال الستعادة غاز البترول المسال والمكثفات المتبقية في الغاز من المرحلة أ )معالجة الغاز واستعادة المكثفات). أدى استغالل حقل رود الناس )الغاز والمكثفات( بمرور الوقت إلى انخفاض ثراء المنتجات الثقيلة. أثر هذا االنخفاض في الثراء على إعدادات تشغيل الوحدة يتمثل عملنا في إجراء حساب تحقق من خالل طريقة التحجيم التقريبية على عمود التقطير (02-T (ومقارنة النتائج التي تم الحصول عليها مع التصميم ، لضمان األداء الصحيح للعمود. الكلمات المفتاحية : غاز البترول المسال ، المكثفات ، عمود التقطير )02-T ، )طريقة التحجيم التقريبية."
Génie Pétrochimie مذكرة ماستر تخصص
Keywords: Keywords: LPG, Condensate, Debutanizer column (T-02), Approximate sizing method.; الكلمات المفتاحية : غاز البترول المسال ، المكثفات ، عمود التقطير )02-T ، )طريقة التحجيم التقريبية.